2007
DOI: 10.1177/0040517507081283
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Scaffolds for Tissue Engineering by Flock Technology

Abstract: Flock technology is a method well known in the textile industry. Short fibers are applied almost vertically on a substrate, coated with a flocking adhesive. Until now, this technology has not been used in the field of biomaterials. Our aim was to use electrostatic flocking for fabricating a novel type of scaffolds for tissue engineering. This method offers the possibility to create matrices with anisotropic properties that have a high compressive strength despite high porosity. First, experiments were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…3 Principle of electrostatic flocking. In the traditional flocking used in textiles industry, the electrostatic field used was 40,000 V whereas in the flocking for scaffold production, the electrostatic field required is 60,000 V. 73 …”
Section: Principle Of Electrostatic Flockingmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Principle of electrostatic flocking. In the traditional flocking used in textiles industry, the electrostatic field used was 40,000 V whereas in the flocking for scaffold production, the electrostatic field required is 60,000 V. 73 …”
Section: Principle Of Electrostatic Flockingmentioning
confidence: 99%
“…In another work done by Walther et al, it was observed that during cultivation for seven days on flocked scaffolds, 7F2 osteoblasts proliferated with higher rates, which was evident from 15-fold increase of Lactate Dehydrogenase (LDH) 73. In addition to that, SEM images of flock scaffolds seeded with cells demonstrated a significant increase in cell number in comparison to day 1.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In case of cartilage damage, anisotropic scaffolds with parallel fiber orientation which provide columnar pore channels represent a suitable approach [4]. These types of scaffolds can be developed by flock technology [5]. Electroflocking is the process of applying short fibers to a substrate covered with an adhesive [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its suitable application for fabricating ordered fibrous structures, electroflocking has not been yet widely considered to produce scaffolds for TE. Only few studies are available in literature [4,5,7]. Walther et al [7], for example, showed that chondrogenesis of mesenchymal stem cells (MSC), which is determined by the synthesis of proteoglycan and deposition of collagen type II, was significantly higher on flock scaffolds than when cultivated in collagen gels.…”
Section: Introductionmentioning
confidence: 99%